Room2Educ8: A Framework for Creating Educational Escape Rooms Based on Design Thinking Principles - Panagiotis Fotaris; Theodoros Mastoras (MDPI AG, 2022)
By immersing learners in a playful, interactive, and engaging experience, Educational Escape Rooms (EERs) have been found to enhance learners' motivation, help them to develop 21st century skills, and improve knowledge acquisition. As research into EERs is still in a preliminary phase, no unified framework about how to design them has been established yet. Additionally, existing frameworks rarely validate the quality and efficacy of the frameworks themselves in terms of usability and usefulness. Therefore, the present paper proposes Room2Educ8, a learner-centred framework for EER design that follows Design Thinking principles. It provides detailed heuristics for empathising with learners, defining learning objectives and constraints, adding narrative, designing puzzles, briefing and debriefing participants, prototyping and playtesting, documenting the whole process, and evaluating the EER experience. A mixed-methods internal validation study based on Instructional Design model validation was conducted with 104 postgraduate students between 2018-2022 to assess the framework's integrity and use. The study findings suggest that Room2Educ8 can be proposed as a valid tool for developing a wide range of EER types that cover a variety of topics. Its well-described and practical steps make it appropriate for educators regardless of a lack of prior experience in EER design.